Meningkatkan Literasi Keuangan Syari’ah Melalui Edukasi Rutinan Jama’ah Ibu-Ibu Pengajian - Mustafidah, Wiwit; Ustanti, Mira; Aini, Aula Izzatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
The women of the recitation group are the spearhead in managing household finances. Whether household finances are good or bad depends on how a mother manages them. The object of this research is the mothers of the congregation at the Al Falah Sumberagung recitation group. The aim of this research is to increase understanding of sharia financial literacy so that it can increase sharia financial inclusion. The method in this research uses quantitative methods with data collection techniques by distributing questionnaires to 54 respondents. The results show that before the education was carried out, the sharia financial literacy level of the recitation mothers was 40%, whereas after the education was carried out the sharia financial literacy level increased to 65%. This shows the importance of education/socialization to the community as a whole to increase sharia financial literacy.